Adaptation Strategy of MSME (Micro, Small and Medium Enterprises) Actors in The Middle of Covid Pandemic (Study in Surabaya and Sidoarjo) - Diyah Utami; Mutiah Mutiah; Arief Sudrajat (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
This study aims to see the impact of the COVID pandemic on a group of people, namely MSME (Micro, Small and Medium Enterprises) actors. This entrepreneurial sector is known for its flexibility and resilience to withstand all situations and conditions, including during the 1998 monetary crisis. However, during the pandemic, this sector was hit the hardest compared to large companies. This is because the MSME sector in general does not have large savings as part of a precautionary motive. The government actually already has an assistance program for MSMEs affected by COVID. But, of course, MSME (Micro, Small and Medium Enterprises) actors must rise up to help themselves, not only relying on government programs that may have limitations. This study aims to see the strategies of the MSME actors, both economic and social strategies. Researches on the adaptive strategies of economic actors have indeed been carried out frequently. The difference is that the adaptive strategy that will be examined this time is a strategy during the COVID pandemic. Most of the COVID-19 studies have been conducted in the medical or health sector. Because this research was conducted during the pandemic, interviews were conducted through digital technology, namely WA calling or telephone. There were six research subjects who were interviewed, with various product variants produced. Based on the research results, it was found that there are three kinds of adaptation strategies for MSME actors namely: economic strategy, technology strategy and social network strategy.